The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1242/jcs.140657
|View full text |Cite
|
Sign up to set email alerts
|

Distinct c-Met activation mechanisms induce cell rounding or invasion through pathways involving integrins, RhoA and HIP1

Abstract: Many carcinomas have acquired oncogenic mechanisms for activating c-Met, including c-Met overexpression and excessive autocrine or paracrine stimulation with hepatocyte growth factor (HGF). However, the biological outcome of c-Met activation through these distinct modes remains ambiguous. Here, we report that HGF-mediated c-Met stimulation triggers a mesenchymal-type collective cell invasion. By contrast, the overexpression of c-Met promotes cell rounding. Moreover, in a high-throughput siRNA screen that was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…Interestingly, PDGF has also been implicated in integrin endocytosis from CDRs, actin-dependent structures at the dorsal cell surface, by macropinocytosis (Gu et al, 2011), suggesting that context-dependent responses of integrins to growth factors exist. In another study, HGF has been shown to induce rapid β1 integrin endocytosis to drive protease- and integrin-dependent collective cell migration in 3D Matrigel in a process requiring clathrin, RhoA and the clathrin adaptor HIP1 (Mai et al, 2014). HIP1 in complex with the clathrin light-chain has also been shown to be necessary for the recycling of the endocytosed inactive integrin and to promote cell migration in fast-migrating lung cancer cells (Majeed et al, 2014).…”
Section: Heterodimer Specificity Of Integrin Traffic In Cell Migratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, PDGF has also been implicated in integrin endocytosis from CDRs, actin-dependent structures at the dorsal cell surface, by macropinocytosis (Gu et al, 2011), suggesting that context-dependent responses of integrins to growth factors exist. In another study, HGF has been shown to induce rapid β1 integrin endocytosis to drive protease- and integrin-dependent collective cell migration in 3D Matrigel in a process requiring clathrin, RhoA and the clathrin adaptor HIP1 (Mai et al, 2014). HIP1 in complex with the clathrin light-chain has also been shown to be necessary for the recycling of the endocytosed inactive integrin and to promote cell migration in fast-migrating lung cancer cells (Majeed et al, 2014).…”
Section: Heterodimer Specificity Of Integrin Traffic In Cell Migratiomentioning
confidence: 99%
“…However, it is clear that endosomal adaptors and scaffold proteins are key mediators of the coordinated traffic of these receptors and, interestingly, some of these adaptors, such as RCP or tensin-4, are upregulated in carcinomas (Muharram et al, 2014; Zhang et al, 2009). Furthermore, regulation of the activity of the Rho family of small GTPases, including Rac1 and RhoA, which are crucial downstream effectors of integrin signalling, has been linked to integrin traffic and is a key factor in determining cell shape, mobility and invasive capacity in many different cancer types (Jacquemet et al, 2013; Mai et al, 2014). Several studies have now established important regulatory steps in integrin traffic that determine whether the receptor is recycled or targeted for degradation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a new paradigm is emerging with the identification of distinct phenotypes elicited whether Met is activated via its overexpression or by the binding of its ligand (61). All these novel insights in Met action will probably lead to a better understanding of Met complex activity in cancers.…”
Section: Perspectivesmentioning
confidence: 99%
“…However, in situ, mammary luminal cells do not express HGF, suggesting that Met signaling in mammary epithelial cells is activated in a paracrine manner. HGF-mediated paracrine and autocrine Met stimulation can trigger distinct biological responses in epithelial cells ( Mai et al, 2014 ). How Met-expressing luminal progenitors respond to the physiological paracrine action of HGF has not yet been investigated at the cellular and molecular levels.…”
Section: Introductionmentioning
confidence: 99%